Optimal distribution transformer size and location by customer location load clustering using improved K-means technique - Templo, Pedro Bernardo M.
This project implements data clustering as a method of grouping customer loads of a Distribution Utility, to calculate the optimal size and location of distribution transformers(DTs). The method used in GIS (Geographic Information Systems) data Fang Wang and Q.J. Zhang's improved k-means algorithm. Results showed reduced lifetime costs per iteration. The algorithm terminates when the costs, which are a function of the length of distribution lines and total load demand, cannot be further reduced. The final output then shows the recommended location and sizing of the distribution transformers. DT location is based on centroid location whereas DT sizing is based on the customer loads clustered to it.